Bio‐Based and Degradable Food Packaging Materials: Where Are They? - Maria G. Bauer; Fabio Henkel; Ufuk Gürer; Oliver Lieleg (Advanced Materials Interfaces)
Abstract In the 1960s, the Swedish company Celloplast patented the first one‐piece plastic bag for packaging, and such plastic bags are heavily used all around the world until they are banned by some countries for environmental and sustainability reasons. Similarly, the EU banned certain single‐use plastic items in 2021—but food packaging is not part of this new regulation. And indeed, the majority of food packaging encountered today in the supermarket is still made from traditional, petrol‐based plastics. This review summarizes recent efforts in developing more sustainable alternatives to such petrol‐based food packaging. Different natural sources and production processes used to develop biodegradable, biopolymer‐based materials (bbMs) are discussed, which are categorized into natural bbMs, modified/plasticized bbMs, and plastic bbMs. An overview of the material properties of commercially available bbMs and bbMs developed in academic research projects is provided, and are compared with the properties of conventional, petrol‐based materials used for packaging. Furthermore, the role of academic and industrial contributors along the value chain of bbMs is highlighted and challenges that are responsible for the still limited occurrence of bbMs in daily lives are discussed.